The effects of Baduanjin exercise on the subjective memory complaint of older adults: A randomized controlled trial. Issue 30 (30th July 2021) - Su, Hong; Wang, Haina; Meng, Lina
Abstract : Abstract: This study aimed to explore the efficacy of Baduanjin exercise on promoting memory function, executive function and general self-efficacy, decreasing the level of subjective memory complaints of older adults. In this randomized controlled trial, 80 patients were randomly allocated in a 1:1 ratio to 12-week Baduanjin exercise group or 12-week control group. Subjective memory complaint questionnaire, Auditory verbal learning test, Trail Making Test and General Self-Efficacy Scale was used to assess the subjective memory complaint level, memory function, executive function and general self-efficacy level at three times (baseline, after intervention and follow up at 3 months). One-way repeated measures analysis of variance was used to compare the outcome variables of the two groups. There were no significant differences between the Baduanjin exercise and the control group at baseline in demographic, SMCQ, MoCA, and GDS-15. Compared to participants in the control group, participants in the Baduanjin group had a significantly improvement in memory function (F = 46.93, P < .00), executive function (F = 317.83, P < .00) and general self-efficacy (F = 38.72, P < .00) at the end of 12-week intervention period and after 3months follow-up period ( P < .01). At the same time, participants in the Baduanjin group had a significantly greater decrease in subjective memory complaint scores at the end of 12-week intervention period and after 3months follow-up period (F = 24.53, P < 0.00). Baduanjin exercise appears to be a feasible and acceptable intervention to improve subjective memory complaint among older adults.